Utilisation of electrical power : including electrical drives and electric traction - Rajput, R.K (Laxmi Publications (P) Ltd, 2014)
Utilisation of electrical power : including electrical drives and electric traction / Rajput, R.K. -- Kolkata: Laxmi Publications (P) Ltd., 2014 621.3121 R161e2 2nd ed No. of Copies : 1